2022
DOI: 10.3389/fpubh.2022.966714
|View full text |Cite
|
Sign up to set email alerts
|

Associations between psycho-behavioral risk factors and diabetic retinopathy: NHANES (2005–2018)

Abstract: of DR should also be paid attention. Our study highlights that mild and moderate depression and ≤ h of sleep are distinguishably associated with DM complicated with DR. It indicates that psycho-behavioral risk factors confer a vital influence on diabetic health care and DR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…Many domestic research on the burden of treatment for diabetic patients has focused on financial, family, and psychological aspects. 36,37 Excessive attention unpleasant emotional experiences or difficulties in follow-up treatment due to various reasons while neglecting the burden of the patient's inability to tolerate their current medication in the context of the need for long-term or lifelong medication. Meanwhile, during the survey, we found that only 8.5% of respondents regularly monitored their blood sugar, which was much lower than that in Western countries, indicating that Chinese T2DM patients should pay more attention to this aspect.…”
Section: Discussionmentioning
confidence: 99%
“…Many domestic research on the burden of treatment for diabetic patients has focused on financial, family, and psychological aspects. 36,37 Excessive attention unpleasant emotional experiences or difficulties in follow-up treatment due to various reasons while neglecting the burden of the patient's inability to tolerate their current medication in the context of the need for long-term or lifelong medication. Meanwhile, during the survey, we found that only 8.5% of respondents regularly monitored their blood sugar, which was much lower than that in Western countries, indicating that Chinese T2DM patients should pay more attention to this aspect.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to LS7, LE8 score is a more composite score that includes sleep as a new component of CVH [6,31] . Although the relationship between the comprehensive level of CVH and DR remains unexplored, diet, physical activity, intake of nicotine, sleep, obesity, and diabetes have been proven to be related to DR [32][33][34][35][36] . A further study has shown that LE8 scores is signi cantly associated with premature mortality, particularly among individuals with type 2 diabetes (T2D) [37] .…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, earlier disease detection and DR prevention are made possible by improved diabetes diagnosis and management D standards. Potential psychological stress may accelerate the progression of DR through biological pathways (9) or through behavioral pathways (10), which can result in poor blood sugar control and increase the risk of DR. On the other hand, psychological factors are significantly related to the occurrence and development of DR (11), active diabetes health management, psychological intervention, and DR can be slowed down (12). In order to prevent and treat visual impairment as well as manage diabetes holistically, it is important to pay attention to psychological aspects and their underlying mechanisms and to act quickly.…”
Section: Epidemiology Of Diabetic Retinopathymentioning
confidence: 99%